HISTORICAL-PHILOSOPHICAL-LEGAL RESEARCH OF THE PHENOMENON OF THE GENDER AS THE FACTOR OF THE SOCIAL STATUS OF THE UKRAINIAN WOMAN - H. F. Moskalyk; M. Y. Baranovska; M. O. Bulach (Antropologìčnì Vimìri Fìlosofsʹkih Doslìdžen')
Topicality. Under the conditions of Ukraine’s integration into the European community, there is an urgent need to restructure all social institutions, freeing them from all forms of discrimination, including on the basis of gender. Modern problems of the state's socioeconomic development require a new look at the functional roles of men and women, as well as the understanding that the political, economic, cultural future of society depends on overcoming gender stereotypes that are deeply rooted in the social and individual consciousness and inhibit social progress, and also the development of democracy. That is why, today, it is extremely important to study the issue of social influence and the role of women and determine their social status against the backdrop of the historical development of our state. Purpose. The article studies the emergence and adoption of the phenomenon of gender as a factor of the social status of the Ukrainian woman in the historical, philosophical and legal realm. Methodology. In the research process the authors used the methods of analyzing and synthesizing historical sources to study the content and main provisions of philosophical concepts and legal norms that formed the social status of a Ukrainian woman at different historical periods of society development, with their subsequent comparison and generalization. Originality. The work further develops the theory of gender processes with the use of interdisciplinary approaches to the study of the phenomenon of gender in the historical, philosophical and legal field as a factor of the social status of the Ukrainian woman, to critically re-evaluate the value guidelines on the construction of modern society and the formation of new ideas about the role and model of behavior of men and women and their interaction in society. Conclusions. For a long time, the social status of women was formed under the influence of philosophical views and concepts, slowly turned into the moral traditions of peoples and the rule of law. The high status of a woman, as a full-fledged member of society, formed in the early state stages, lost its relevance already in the days of antiquity. The woman became a symbol of exclusively domestic, family relations and played the role of guardian of the private foundations of the social being of men. This trend found its continuation in the Roman Empire, significantly increased in the Middle Ages and left an imprint in the philosophy of modern times and German classical philosophy. In the period from Kievan Rus to the twentieth century, the Ukrainian woman remained a victim of stereotyped thinking. Despite the normative settlement of the equality of men and women in modern conditions, this equality has a purely declarative nature.